ChemInform Abstract: A Convenient Approach for the Synthesis of 2, 6‐Diformyl‐ and 2, 6‐Diacetylpyridines. Issue 16 (28th March 2013) - Ivchenko, Pavel V.; Nifant'ev, Ilya E.; Buslov, Ivan V.
Abstract Pyridine dicarboxamides (I) are suitable substrates for the synthesis of diacetyl‐ and diformylpyridines via reduction with methylmagnesium chloride or reduction with lithium aluminum hydride, respectively.